Factors Affecting Audit Delay in Manufacturing Companies - Arie Pratania Putri; Gidion Alexsyan Sujoyo Sitompul; Elmi Rovita Manalu (Budapest International Research and Critics University, 2022)
The pupose of this study is to find out the extent to which the variabels of Company Size, Profitability, Audit Opinion, Company Age, Solvency, and Audit Committee are related to Audit Delay. Population data taken from manufacturing service companies listed the IDX in 2017-2019. The sample was taken using a purposive sampling technique, using a sample of 37financial reports. The technique for data analysis used linear moderation regression analysis using the SPSS 24 program. Where there is a time diffrence between the financial statements and the audit date, it can indicate the length of time in the settlement audit period.